Isolation and Identification of Facultative Anaerobic Bacteria from Feces of Pet Dogs (Medico Legal Update, 2020)
A fifty fecal swabs (25 from Anbar province and 25 from Salahuddin province) were collected from both sexes dogs with different global breeds, different ages. These swabs were cultured onto blood , nutrient and MacConkey agars, then the colonies were purified on nutrient and MacConkey agars. A gram stain and biochemical tests were done including catalase, oxidase and TSI. The results of isolation and identification showed that Salmonella spp. were isolated from 5 out of 14 puppies (35.7%), while E. coli from 9 (64.3%) and Serratia spp. from 1(7.1%), whereas, from adults , salmonella spp. isolated from 9 (25%) dogs and E. coli from 24 (66.7%) out of 36 adult dogs.It is concluded that Salmonella spp. and E. coli are the most prevalent in asymptomatic dogs and puppies in Anbar province and Salahuddin which means that the dogs are a reservoir for these bacteria and it is considered as a bad indication for transmission of this pathogen to human being and other animals.